Effect of Task-Correlated Physiological Fluctuations and Motion in 2D and 3D Echo-Planar Imaging in a Higher Cognitive Level fMRI Paradigm - Ladstein, Jarle; Evensmoen, Hallvard R.; Håberg, Asta K.; Kristoffersen, Anders; Goa, Pål E. (Frontiers in Neuroscience, 2016)
Purpose: To compare 2D and 3D echo-planar imaging (EPI) in a higher cognitive level fMRI paradigm. In particular, to study the link between the presence of task-correlated physiological fluctuations and motion and the fMRI contrast estimates from either 2D~EPI or 3D~EPI datasets, with and without adding nuisance regressors to the model. A signal model in the presence of partly task-correlated fluctuations is derived, and predictions for contrast estimates with and without nuisance regressors are made. Material and Methods: Thirty-one healthy volunteers were scanned using 2D EPI and 3D EPI during a virtual environmental learning paradigm. In a subgroup of 7 subjects, heart rate and respiration were logged, and the correlation with the paradigm was evaluated. FMRI analysis was performed using models with and without nuisance regressors. Differences in the mean contrast estimates were investigated by analysis-of-variance using Subject, Sequence, Day, and Run as factors. The distributions of group level contrast estimates were compared. Results: Partially task-correlated fluctuations in respiration, heart rate and motion were observed. Statistically significant differences were found in the mean contrast estimates between the 2D EPI and 3D EPI when using a model without nuisance regressors. The inclusion of nuisance regressors for cardiorespiratory effects and motion reduced the difference to a statistically non-significant level. Furthermore, the contrast estimate values shifted more when including nuisance regressors for 3D EPI compared to 2D EPI. Conclusion: The results are consistent with 3D EPI having a higher sensitivity to fluctuations compared to 2D EPI. In the presence partially task-correlated physiological fluctuations or motion, proper correction is necessary to get expectation correct contrast estimates when using 3D EPI. As such task-correlated physiological fluctuations or motion is difficult to avoid in paradigms exploring higher cognitive functions, 2D~EPI seems to be the preferred choice for higher cognitive level fMRI paradigms.